2018
DOI: 10.1093/pm/pny074
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in the Evaluation and Management of Pain in the Outpatient Setting, 2006–2015

Abstract: Identifying causes of racial and ethnic disparities in the evaluation and treatment of pain in the outpatient setting is important to improving the health and function of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 20 publications
5
49
2
Order By: Relevance
“…Despite statistically significant differences in age, insurance status, perineal lacerations, and BMI at time of delivery, inpatient postpartum use of oxycodone 5 mg tablets was nearly identical between Black and White patients. This is in contrast to the findings of other institutions, which note significant differences in opioid prescription practices both in the postpartum period and in numerous other specialties and situations between Black and White patients [ 8 , 10 , 11 ]. In addition, we found that the amount of opioid tablets prescribed at discharge were not associated with patient race.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite statistically significant differences in age, insurance status, perineal lacerations, and BMI at time of delivery, inpatient postpartum use of oxycodone 5 mg tablets was nearly identical between Black and White patients. This is in contrast to the findings of other institutions, which note significant differences in opioid prescription practices both in the postpartum period and in numerous other specialties and situations between Black and White patients [ 8 , 10 , 11 ]. In addition, we found that the amount of opioid tablets prescribed at discharge were not associated with patient race.…”
Section: Discussioncontrasting
confidence: 99%
“…Male patients report more time spent with clinicians during health care visits, 37 while women report less positive experiences with provider communication regarding medication management. 38 Further, non-Caucasians continue to experience potential bias 39,40 and report poor quality of care. 41 Non-Caucasians, particularly African Americans, are subject to shorter office visits, 42,43 resulting in the reduction of key activities that may influence self-care.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the ndings of other institutions, which note signi cant differences in opioid prescription practices both in the postpartum period and in numerous other specialties and situations between Black and White patients. 8,10,11 In addition, we found that the amount of opioid tablets prescribed at discharge…”
Section: Discussionmentioning
confidence: 83%